Monitoring of high energy deuteron beams in the experiments with massive targets - Artiushenko, M.Yu.; Voronko, V.A.; Petrusenko, Yu.T.; Rozhkov, V.A.; Sotnikov, V.V.; Zhadan, A.A.; Tyutyunnikov, S.I.; Furman, W.I.; Chilap, V.V.; Chinenov, A.V. (Вопросы атомной науки и техники, 2014)
The influence of massive uranium target (500 kg natU) of assembly "QUINTA" on the results of high energy deuteron
beam monitoring with aluminum and copper foils was investigated. In order to increase the accuracy of deuteron
beam off-line monitoring, the measurements of the cross sections of fragmentation reaction natCu(d,x)24Na
were performed at 1.32, 2, 4 и 8 GeV deuteron energies. For the same deuteron energies the cross sections of residual
nuclei 7
Be, 42K, 52Mn, 57Co and 58Co for natCu(d,x) reaction were measured Исследовано влияние массивной урановой мишени (500 кг natU) установки «КВИНТА» на результаты мониторирования пучков дейтронов с помощью алюминиевых и медных фольг. Для улучшения точности off-line мониторирования пучков дейтронов, бомбардирующих протяженные мишени из тяжёлых элементов, были проведены измерения сечений реакции фрагментации natCu(d,x)24Na для дейтронов с энергией 1,32; 2; 4 и 8 ГэВ. Для этих же энергий дейтронов измерены сечения выхода изотопов 7 Be, 42K, 52Mn, 57Co и 58Co в реакциях natCu(d,x). Досліджено вплив масивної уранової мішені (500 кг natU) установки «КВІНТА» на результати моніторування пучків дейтронів за допомогою алюмінієвих і мідних фольг. Для покращення точності off-line моніторування пучків дейтронів, які бомбардують протяжні мішені з важких елементів, були проведені вимірювання перетинів реакції фрагментації natCu(d,x)24Na для дейтронів з енергією 1,32; 2; 4 і 8 ГеВ. Для цих же енергій дейтронів виміряні перетини виходу ізотопів 7 Be, 42K, 52Mn, 57Co в реакціях natCu(d,x).